Investigating the indirect impact of transformational leadership on performance and work alienation: evidence from school principals navigating COVID-19 - Roche, Joseph (My University, 2024)
Purpose – Although significant research has examined the concept of transformational leadership, few studies have explored the indirect impact of transformational leadership on individual and organizational outcomes within the context of crisis. Accordingly, this study aims to advance our understanding of the indirect impact of transformational leadership on school performance and principals’ work alienation within the context of the COVID-19 pandemic. In doing so, this study contributes to this developing stream of literature by hypothesizing the indirect effect of two relational resources, namely employee trust and relational coordination, which mediate the relationship between transformational leadership, school performance and principals’ work alienation. Design/methodology/approach – This study draws on a unique sample of 634 principals from Irish primary schools navigating the COVID-19 crisis. Structural equation modeling (SEM) was performed using Mplus 8.3 to test the hypothesized model. Findings – Mixed findings emerged concerning the mediating process of relational resources and their impact on transformational leadership, school performance and principals’ work-alienation. In particular, support is found for the critical role of principals whose transformational leadership style can help increase school performance. However, evidence suggests that employee trust does not mediate the relationship between transformational leadership and principals’ work alienation. Practical implications – This study provides several practical insights for education professionals, policymakers and HRM practitioners across each phase of the crisis management cycle. Firstly, regarding the pre-crisis stage, educational institutions should invest in targeted leadership development programs that prioritize relationship-building and effective communication among stakeholders. Second, during crises, the study emphasizes the role of relational resources in mediating the impact of leadership on school performance. Moreover, the study illustrates the importance of proactively cultivating strong connections with stakeholders, fostering timely, problem-solving-based communication. Finally, in the post-crisis phase, collaboration with government stakeholders is recommended to inform recovery policies. Originality/value – This study makes several contributions to the literature on leadership and crisis management. First, this study adds new insights suggesting how principals as leaders influence school performance during crisis. Second, by adopting a relational perspective, this study suggests two types of relational resources (i.e. employee trust and relational coordination), as the mediators between transformational leadership, school performance and principals’ work alienation. Third, this study moves the existing research on leadership during crisis forward by focusing on the functional effectiveness of leadership while focusing on the principals’ work alienation during the pandemic.
PUBLISHED
Keywords: Transformational leadership, School performance, Work alienation, Relational resources, COVID-19; Educational Leadership and Management